High School with Technological Intermediation (EMITec): analysis of the curriculum proposal - Carneiro, Eudite Fernandes; Eugenio, Benedito Gonçalves (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
This article presents the results of a research that investigated the curriculum policy for high school in the State of Bahia. The focus of the text is the evidence of the recontextualization process present in the curricular policy of the proposal of High School with Technological Intermediation (EMITec). We present an overview of the program, highlighting the curricular organization and emphasize some discussions about the influences present in the production of EMITec's discourse. For this, we go through some fundamental concepts of the theory of the pedagogical device of Basil Bernstein (1996; 1998), especially his production on the pedagogical recontextualization of the speeches. Based on the notes made, we can infer that the recontextualizing principles printed to EMITec produce new and different discourses.